The Labour Supply of Women in STEM - Eva Schlenker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The purpose of this paper is to assess the determinants of female labour supply in science, technology, engineering and mathematics (STEM). Using data from the European Statistics on Income and Living Conditions (EU-SILC), the author finds that women in STEM work more hours, but have a higher probability to be out of the labour force. Additionally, empirical evidence is found that maternal employment in STEM is also significantly more pronounced. To account for selection problems, a special type of grouping estimator and a control function approach is used. The estimation results show, that women in STEM work less hours in countries with higher levels of family allowances. However, this effect is only weakly significant and small compared to the overall effects of larger levels of expenditures on family allowance and child benefits.
Keywords: J22; J24; J16; 330